(untitled) (Economics and region, 2019)
The theoretical apparatus of a new institutional and neo-institutional theory in the field of land economics is reinterpreted. The necessity of further institutional development of land relations in Ukraine is determined in the article. Institutional securement of domestic land policy is «a barometer» of assessing the attitude of society to land benefits, and the attitude to the land of the main public institute – the state, an assessment of stability of the state on a geopolitical scale.